EFFECT OF HYDROGEN PEROXIDE ON PIGMENT COMPOSITION AND CHLOROPHYLL FLUORESCENCE IN BASIL (OCIMUM BASILICUM L.) LEAVES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Basil is one of the most famous herbs, widely used fresh, and for therapeutic and pharmaceutical purposes. Basil has recently been shown to rank first among spices and herb crops regarding xanthophyll-carotenoids, which are associated with a reduced risk of cancer and age-related eye diseases. Given the widespread use of the herb basil in nutrition and herbal medicine, the contents of its leaves are of obvious interest. However, some studies say that water enriched with hydrogen peroxide helps more effectively saturate plant cells with oxygen molecules, activates the growth processes of all parts of seedlings, and increases the resistance of seedlings to various unfavorable factors, including dangerous fungal and bacterial diseases (late blight, downy mildew, root rot, powdery mildew, bacteriosis). However, in high concentrations, hydrogen peroxide also can have a phytotoxic effect on plants. The research goal for the current study was to determine the application of hydrogen peroxide (H2O2) on photosynthetic processes (the content of photosynthetic pigments, the parameters of the chlorophyll a fluorescence) in sweet basil (Ocimum basilicum L. cv. “Genovese”). The experiment was carried out under controlled conditions with three replications. Four treatments of H2O2 were tested: 0.0, 0.1, 0.5, 1.0 and 3.0%. Both photosynthetic pigments and parameters of the chlorophyll a fluorescence in basil leaves were quantified and compared with the control.  The plants were cultivated in an environmental climatic chamber with conditions close to real natural conditions (temperature: 24-30°C, humidity: 70 – 80%, photoperiodism: day/night (8/16), illumination: 10 000 lux). The present results revealed the changes in chlorophyll fluorescence parameters in basil under different concentrations of H2O2 (0.1, 0.5, 1.0 3.0%). In addition, changes in photosynthetic pigment composition have also been noticed depending on the concentrations of H2O2 in the water before watering the plants. However, it is necessary to continue studying the effect of H2O2 on the whole plant in future research.